Inorganik Waste Management Based On Hand Craft Of Plastic Waste With Economic Value In Indonesia - Siti Nurwahidah; Syahdi Mastar; Heri Kusnayadi; Nila Wijayanti (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2020)
Population and economic growth lead to the increase of waste production, especially inorganic waste. Usually inorganic waste is burned to remove it from view. In fact, if the combustion is incomplete (under 8000 C) it can form dioxins, which are compounds that can trigger cancer, hepatitis, hepatomegaly, and nervous system disorders. Student Community Service - Community Service Learning (KKN-PPM) aims to invite the public to reduce inorganic waste, especially plastic waste, by recycling it into goods which have economic value. The existence of the Jurumapin Village Garbage Bank Office provides media for the Jurumapin Village community in managing, buying and selling waste. Handicraft products processed by the Student Community Service - Community Service Learning (KKN-PPM) of Samawa University such as wallets, water baskets, fruit plates, market baskets and ecobrick chairs.